Chronic treatment with resveratrol, a natural polyphenol found in grapes, alleviates oxidative stress and apoptotic cell death in ovariectomized female rats subjected to chronic cerebral hypoperfusion. (20th April 2016) - Ozacmak, Veysel Haktan; Sayan-Ozacmak, Hale; Barut, Figen
Abstract : Objectives : Resveratrol appears to have neuroprotective potential in various animal models of brain disorders including cerebral ischemia and neurodegenerative diseases. Chronic cerebral hypoperfusion is a well-known pathological condition contributing to the neurodegenerative diseases such as vascular dementia. Purpose of the present study is to evaluate the possible therapeutic potential of resveratrol in a model of vascular dementia of ovariectomized female rats. Assessment of the potential was based on the determination of brain oxidative status, caspase-3 level, glial fibrillary acidic protein (GFAP), and neuronal damage on hippocampus and cerebral cortex. Methods : For creating the model of chronic cerebral hypoperfusion, ovariectomized female Wistar rats were subjected to the modified two vessel occlusion method, with the right common carotid artery being occluded first and the left one a week later. Results : At the 15th day following the ligation, neuronal damage was accompanied by the increased immunoreactivities of both GFAP and caspase-3, and significant neurodegeneration was evident in the hippocampus and cortex, all of which were significantly alleviated with resveratrol treatment (10 mg/kg). Biochemical analysis revealed that the resveratrol treatment decreased lipid peroxidation and restored reduced glutathione level as well. Discussion : The collected data of the present study suggest that the administration of resveratrol may provide a remarkable therapeutic benefit for vascular dementia, which is most likely related to the prevention of both apoptotic cell death and oxidative stress. We believe that therapeutic efficacy of resveratrol deserves to be tested for potential clinical application in postmenopausal elderly women suffering from vascular dementia.